ANALYSIS OF QURANIC RECITATION IN INTERFAITH DIALOGUE: Broadcasting and Islamic Law Perspectives - Asmara, Devi Sastika Wiramaya; Fathurrijal, Fathurrijal; Sukarta, Sukarta; Nasir, Badlihisham Bin Mohd (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
Media framing will consciously or unconsciously select information and accentuate certain aspects to shape public perception of an event. This research aims to analyze the framing of the recitation of the Qur'an in the context of interfaith dialogue, particularly on the occasion of Pope Francis' visit to the Istiqlal Mosque. Through a descriptive qualitative approach, this research examines in depth how the media, in this case Kompas TV, presented the event. The analysis is focused on the perspective of broadcasting law and contemporary Islamic law. The results show that the practice of reciting the Qur'an in the context of interfaith dialogue has great potential in promoting the values of tolerance and pluralism. However, there are different views among scholars regarding the limits of this practice. Legally, although there is no specific regulation, the general principles in the Broadcasting Law provide room for the practice. Meanwhile, from the perspective of Islamic law, there are differences of opinion among scholars regarding the permissibility of this practice. Qur'anic recitation in the context of interfaith dialogue can be an effective means of building better understanding between religious communities. However, it is important to maintain a balance between the spirit of inclusiveness and the prevailing religious principles. This study will identify the common ground and differences in the perspectives of the two legal systems, as well as their implications for the practice of broadcasting Qur'anic recitations in public spaces.